Energy Concentration and Phosphorus Digestibility in Hatchery Byproducts Fed to Nursery Pigs - Jung Yeol Sung (Animals, 2019)
The objective was to measure energy concentrations and standardized total tract digestibility (STTD) of phosphorus (P) in hatchery byproducts. In Experiment 1, 20 nursery barrows were used to measure energy concentrations in hatchery byproducts. A basal diet based on corn and dried whey and four additional diets containing 25% of infertile eggs, unhatched eggs, culled chicks, or a mixture of the three hatchery byproducts were prepared. In Experiment 2, the STTD of P was measured using 20 nursery barrows. Four diets containing 25% of the same hatchery byproducts used in Experiment 1 as the sole source of P were prepared, and a P-free diet was prepared to measure basal endogenous losses of P. The marker-to-marker method was employed for total collection. Metabolizable energy in culled chicks was the greatest (4560 kcal/kg as-is basis; p < 0.05), whereas infertile eggs had the lowest value (2645 kcal/kg as-is basis; p < 0.05). The STTD of P in infertile eggs (81.7%) was greater than that in unhatched eggs, culled chicks, and the mixture (61.6, 53.9, and 47.4%, respectively; p < 0.05). In conclusion, culled chicks had the greatest metabolizable energy and infertile eggs had the greatest phosphorus digestibility among the test ingredients.